THE CONCEPT OF DIALECTICISM IN THE ITALIAN LANGUAGE - Eldorbek Khusanov (Bright Mind Publishing, 2026)
The article analyzes dialectisms in modern Italian as a complex, multi-level linguistic phenomenon covering phonetics, lexicon, morphology, and syntax. Dialectisms are viewed not as marginal elements, but as an active component of the language system, providing expressiveness, stylistic richness, and regional identity. The study demonstrates their role in forming regional Italian (italiano regionale), in artistic literature, spoken communication, and mass culture, as well as their evolution in the context of globalization and digital communication. The findings highlight the importance of dialectisms for dialectology, sociolinguistics, and the methodology of teaching Italian as a foreign language, and open perspectives for studying their development in modern media.
Keywords: Dialectisms, Italian language, linguistic variation, Italian regional, dialectology, sociolinguistics, identity, literary text, mass culture, globalization.